Cybercrime, Perlindungan Data Warga Negara, dan Integritas Pemilu - Mudjiyanto, Bambang; Launa, Launa; Leonardi, Aska (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
Abstract Theft of personal data ahead of an election is a criminal act that can damage public trust in the election process and results. The development of digital technology (including electronic election practices) has given new hope for the implementation of elections in the era of cyber society. Election technology provides a new space to support cyber society in virtual political activities of digital democracy. This study seeks to explain cybercrime that continues to operate in many countries (including Indonesia), the weak protection of citizens’ data, and its implications for the integrity of the 2024 simultaneous elections. This study is qualitative with a case study approach based on literature review and finds that the development of digital technology will always followed by an increase in data theft crimes (which are motivated by economic motives), weak protection of citizens’ personal data (a serious digital security problem which should be the responsibility of the state), and implications for election integrity due to data leaks which theoretically hackers use as space to delegitimizing state control over the hegemony of digital election technology.Keyword: Cybercrime, data protection, politik and economic implication, election integrity.